Grasslands of the World - Jim Hoy; Larry Patton; Marty White (Symphony in the Flint Hills, 2015)
An introduction to the Grasslands of the World, detailing their importance, explorer's impressions, and human interaction with nature. The Masai [sic] are also a nomadic people whose principal interest and sole wealth are in cattle and goats.
Keywords: grasslands; world; worldwide; international; prairie; plains; map; nature; natural; native; grass; seasonal; continents; The Masai